Is there a duration-characteristic relationship for trypsin exposure on tendon? A study on anterior cruciate ligament reconstruction in a rabbit model - Ma, Rongxing; Gao, Xiaokang; Jin, Yangyang; Wang, Xiaolong; Li, Ruifeng; Qiao, Ruiqi; Wang, Xinliang; Liu, Dayong; Xie, Zhitao; Wang, Limin; Zhang, Jingyu; Xu, Weiguo; et al. (Frontiers in Medicine, 2024)
Background Decellularized allograft tendons are highly regarded for their accessibility and the reduced risk of immune rejection, making them a promising choice for grafting due to their favorable characteristics. However, effectively integrating reconstructed tendons with host bone remains a significant clinical challenge. Purpose This study aims to investigate the relationship between the duration of tendon exposure to trypsin and its impact on tendon biomechanical properties and healing capacity. Methods Morphological assessments and biochemical quantifications were conducted. Allograft tendons underwent heterotopic transplantation into the anterior cruciate ligament (ACL) in a rabbit model, with specimens harvested 6 weeks post-surgery for a comparative analysis of cell adhesion strength and mechanical performance. Duration-response curves were constructed using maximum stress and cell adhesion quantity as primary indicators. Results The trypsin treatment enhanced cell adhesion on the tendon surface. Adhesion rates in the control group vs. the experimental groups were as follows: 3.10 ± 0.56% vs. 4.59 ± 1.51%, 5.36 ± 1.24%, 6.12 ± 1.98%, and 8.27 ± 2.34% (F = 6.755, p = 0.001). However, increasing treatment duration led to a decline in mechanical properties, with the ultimate load (N) in the control vs. experimental groups reported as 103.30 ± 10.51 vs. 99.59 ± 4.37, 93.15 ± 12.38, 90.42 ± 7.87, and 82.68 ± 6.89, F = 4.125 (p = 0.013). Conclusion The findings reveal an increasing trend in adhesion effectiveness with prolonged exposure duration, while mechanical strength declines. The selection of the optimal processing duration should involve careful consideration of the benefits derived from both outcomes.